PARENTAL ACCEPTANCE AND ITS IMPACT ON ENGAGEMENT IN SUPPORT SERVICES FOR CHILDREN WITH SPECIAL NEEDS IN MALAYSIA: A SYSTEMATIC REVIEW - Hassim, Hanifatiah Hanim; Idris, Haliza (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Parental acceptance significantly shapes how families respond to a child’s special needs diagnosis and engage with available support services. In Malaysia, where cultural, religious, and social norms influence parenting decisions, understanding the relationship between acceptance and engagement is vital for developing effective interventions. This systematic literature review (SLR) synthesizes empirical evidence on factors influencing parental acceptance and its impact on service engagement for children with special needs. Using PRISMA guidelines and the SALSA framework (Search, Appraisal, Synthesis, and Analysis), 11 peer-reviewed studies published between 2020 and 2025 were analysed. Studies were sourced from Google Scholar and Semantic Scholar. This was selected based on inclusion criteria focused on Malaysian parental populations and relevance to both acceptance and engagement. Three key themes emerged: (1) emotional and informational factors influencing acceptance, including denial, stigma, and professional communication; (2) patterns of engagement, with early acceptance linked to consistent use of therapy, intervention, and educational services; and (3) sociocultural moderators, such as religious beliefs, affiliate stigma, and disparities in access across urban and rural settings. These findings show that parental acceptance is both an emotional process and a catalyst for meaningful participation in service. This review underscores the importance of culturally sensitive, parent-centered approaches and of integrating emotional support into diagnostic pathways. It also identifies research gaps in longitudinal studies and father-specific perspectives. The findings have practical implications for educators, healthcare providers, and policymakers seeking to strengthen family-centered support systems for children with special needs in Malaysia.